Single Input Fuzzy Controller With Command Shaping Schemes For Double-Pendulum Type Overhead Crane - Mohd Ashraf, Ahmad; Muhammad Salihin, Saealal; Raja Mohd Taufika, Raja Ismail; Mohd Anwar, Zawawi; Ahmad Nor Kasruddin, Nasir; Mohd Syakirin, Ramli (AIP Publishing LLC, 2011)
This paper presents investigations into the development of composite control schemes for trajectory tracking and antisway control of a double-pendulum-type overhead crane (DPTOC) system. A nonlinear DPTOC system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. The proposed method, known as the Single Input Fuzzy Logic Controller (SIFLC), reduces the conventional two-input FLC (CFLC) to a single input single output (SISO) controller. The SIFLC is developed for position control of cart movement. This is then extended to incorporate input shaping schemes for anti-swaying control of the system. The input shapers with different mode selection are designed based on the properties of the system. The results of the response with the controllers are presented in time and frequency domains. The performances of control schemes are examined in terms of level of input tracking capability, sway angle reduction and time response specifications in comparison to SIFLC controller. Finally, a comparative assessment of the control techniques is discussed and presented.